Pengaruh Struktur Modal Dan Pertumbuhan Penjualan Terhadap Nilai Perusahaan Pada Sektor Konsumer - Sairin Sairin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of capital structure and sales growth on firm value in the consumer sector listed on the Indonesia Stock Exchange (IDX). The method used is quantitative research with secondary data in the form of annual financial reports of consumer goods sub-sector companies for the 2018–2023 period. The independent variables in this study are capital structure (DER) and sales growth, while the dependent variable is firm value (PBV). Data analysis technique uses multiple linear regression with classical assumption tests. The results show that capital structure has a significant negative effect on firm value, while sales growth has a positive but not significant effect. These findings indicate that consumer companies need to maintain a healthy debt proportion and increase sales through marketing strategies and market expansion to maximize firm value.